Anti-tissue transglutaminase antibodies from coeliac patients inhibit transglutaminase activity both in vitro and in situ. Issue 2 (1st August 2002) - Esposito, C; Paparo, F; Caputo, I; Rossi, M; Maglio, M; Sblattero, D; Not, T; Porta, R; Auricchio, S; Marzari, R; Troncone, R
Abstract : Background and aims: Coeliac disease (CD) is a multifactorial disorder which has an autoimmune component characterised by the occurrence of disease specific autoreactive antibodies against the enzyme tissue transglutaminase (tTG). The aim of this study was to investigate whether binding of antibodies to the enzyme influences tTG activity. Methods: tTG activity was assayed in the presence of immunoglobulin A (IgA) and immunoglobulin G (IgG) purified from the serum of coeliac patients, CUB 7402 (an anti-tTG mouse monoclonal antibody), and human anti-tTG monoclonal antibodies derived from both intestinal lymphocytes from three patients with CD and from peripheral blood lymphocytes from healthy subjects. For our studies we used calcium treated and untreated recombinant human tTG. Furthermore, the effects of antibodies were determined by immunohistochemical detection of tTG activity in sections of human umbilical cord. Results: IgG and IgA from CD patients inhibited tTG activity in vitro in a dose dependent manner, with a different rate of inhibition among patients. The monoclonal antibody CUB 7402 and human monoclonal antibodies displayed a dose dependent inhibitory effect towards the catalytic activity of the enzyme, both in vitro and in situ. Preincubation of tTG with CaCl2 caused loss of the inhibitory effect due to CUB 7402 but not that caused by human monoclonal antibodies. Conclusions: Purified CD IgA, IgG, as well as human anti-tTG monoclonal antibodies inhibited the enzymatic activity of human tTG both in vitro and in situ.